A comprehensive review: Botany, phytochemistry, traditional uses, pharmacology, and toxicology of Spatholobus suberectus vine stems. (10th August 2023) - Huang, Xiaojun; Fei, Qingqing; Yu, Sheng; Liu, Shengjin; Zhang, Li; Chen, Xialin; Cao, Liang; Wang, Zhenzhong; Shan, Mingqiu
Abstract: Ethnopharmacological relevance: Spatholobus suberectus vine stem (SSVS) is the dried lianoid stem of the leguminous plant, Spatholobus suberectus Dunn, which is mainly distributed in China and some Southeast Asian countries. Due to its notable effects of promoting blood circulation and tonifying blood, regulating menstruation and relieving pain, this phytomedicine has been used in traditional Chinese medicine for hundreds of years. Aim of the study: This review is designed to provide a comprehensive profile of SSVS concerning its botany, traditional uses, phytochemistry, quality control, pharmacology, pharmacokinetics, and toxicology and attempts to provide a scientific basis and future directions for further research and development. Materials and methods: Related document information was collected with the help of databases such as the Web of Science, Science Direct, PubMed, China National Knowledge Infrastructure (CNKI) and Flora of China. Results: SSVS is reported to be traditionally used to treat rheumatic arthralgia, numbness and paralysis, blood deficiency, irregular menstruation and other gynecological diseases. Botanical studies have revealed that there are some confusable varieties in some specific locations with a long history. Additionally, 145 chemical constituents have been isolated and identified from SSVS, including flavonoids, organic acids, terpenoids, lignans, and phenolic glycosides. Pharmacological studies have shown that SSVS has a variety of effects, such as nervous system regulation, and antioxidative, antitumor, antiviral, antidiabetic, and anti-inflammatory effects. However, in regard to the absorption-distribution-metabolism-elimination-toxicity (ADMET) of SSVS, few studies have been carried out, and few articles have been published. Conclusion: With a long history of traditional uses, a variety of bioactive phytochemicals and a wide range of definite pharmacological activities, SSVS is believed to have great potential in clinical applications and further research, development and exploitation. The precise action mechanisms, rational quality control and quality markers, and explicit ADMET routes should be highlighted in the future, which might provide effective help to safely, effectively and sustainably use this herbal medicine. Graphical abstract: Image 1